INTERVAL WAKTU TANAM KACANG TANAH (Archis hipogaea L.) DAN JAGUNG PULUT (Zea mays caratina Kulesh) PADA POLA TANAM TUMPANG SARI TERHADAP PERTUMBUHAN DAN HASIL KACANG TANAH DI LAHAN KERING - Kristono Yohanes Fowo (AGRICA, 2018)
This study aims to determine the timing of proper peanut planting in intercropping cropping patterns with various pulut varieties of corn on the growth and yield of peanuts on dry land. The experimental design using the Split Plot Design consisted of two faktors repeated three times. Treatment of corn variety as the main plot cansisted of thee levels (V1: Local variety, V2: Uri variety, V3: Binthe Pulu variety) while planting time was placed as subplots including (T1: groundnut planted 15 days after planting Corn; T2: groundnut is Corn together with peanut planting, T3: groundnut is planted 15 days before planting Corn) Three replications were performed. Data was collected destructively. The F-test at 5% was used to examine the effect of treatments, while differences across treatments were based on the LSD at 5%. The results of the study showed that there was an interaction between the planting time and variety of varieties to the yield parameters of 100 seeds, whereas separately the treatment of plant time is 15 days before the pulut maize plant and planter simultaneously show the highest yield for the growth variable and yield variable of 2.02; and 2.05 tons ha-¹.